(untitled) (LACCEI, 2024)
The problem of contamination by Construction and Demolition Waste seriously affects the countries of China, the United States, Vienna, Lombardy and Brazil, despite their efforts to manage and reuse it. In Peru, the situation is not different, this is evidenced by the large amounts of RCD accumulated on the periphery of cities, as happens in Trujillo, La Libertad region. Therefore, this research was carried out taking advantage of the RCD and a local vegetable fiber with the purpose of determining the effect of the cattail content on the physical-mechanical properties of the masonry units obtained from these residues. To elaborate these units, the RCDs were collected, selected and crushed, the dosages were improved and the mixture was elaborated according to the experimental procedure detailed in the investigation. The data was collected through the technique of direct observation to laboratory tests. A standard sample, another sample with an increase of 1% of cattails, another sample with an increase of 2% of cattails, and another sample with an increase of 3% of cattails with respect to the mass of the brick were analyzed. It was concluded that, in the dimensional variation and warpage test, the results are within the established parameters, in the flexural modulus of rupture resistance test, high levels of resistance are reached, in the compression resistance test of the units of masonry and in the compression resistance test of the adobe walls do not meet the established parameters, however, in the mortar tensile strength test of the masonry units they do meet the permitted parameters. It is recommended to use cement as a mortar instead of earth and sand to improve resistance properties, and to evaluate new local plant fibers.